Seawater acidification and temperature modulate anti-predator defenses in two co-existing Mytilus species. (August 2019) - Kong, Hui; Clements, Jeff C.; Dupont, Sam; Wang, Ting; Huang, Xizhi; Shang, Yueyong; Huang, Wei; Chen, Jianfang; Hu, Menghong; Wang, Youji
Abstract: The effects of short-term (7 days) experimental ocean acidification (−0.4 pH units) and warming (+5 °C) on anti-predator defenses of two sympatric Mytilus species from China, M. coruscus and M. edulis, in the presence and absence of predator cues were investigated. Results suggested species-specific independent negative effects of acidification and warming on the number and weight of byssal threads, the force of thread attachment, and total thread plaque area. Similar negative effects were observed for clustering behaviour, with acidification and warming independently increasing the number of solitary individuals and decreasing the percentage of mussels in clusters. Acidification effects on byssus were strongly exacerbated when predators were present. Ultimately, this study suggests that short-term exposure to experimental warming and acidification can negatively impact anti-predator defense strategies in mussels with potential ramifications for predator-prey interactions and ecological functioning in systems where mussel beds play a key ecological role. Graphical abstract: Unlabelled Image Highlights: Predator, pH and temperature affected the mussels' anti-predator behaviour. Species specific effects were observed between Mytilus coruscus and Mytilus edulis . Low pH and high temperature reduced the anti-predation performance of mussels. Predator induced mussel clustering while low pH and warming had negative effects.